Ekstraksi Fitur pada File Gambar dengan Metode Fast Fourier Transform - Prasetiyowati, Maria Irmina (Faculty of Computer Science, University of Jember, 2024)
There are several methods for performing feature extraction, one of which is the Fast Fourier Transform (FFT). FFT is an effective way to convert signals or time series data to the frequency domain. This study uses the FFT method for image data. Image data is transformed using FFT and returned using the Inverse Fast Fourier Transform (IFFT). From the results of the feature extraction test on nine image files, it was found that 78% of the image data experienced a decrease in size, 11% of the images had a fixed size, and 11% of the image data experienced an increase in size.